Exploring the Factors Influencing User Attitudes and AI Chatbot Use in the Tourism Sector: Evidence from Indonesia - Ariendy Filrando; Renza Fahlevi; Fitriana Aidnilla Sinambela (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study investigates the influence of perceived ease of use, perceived usefulness, perceived trust, anthropomorphism, and personalization on user attitudes, and how these attitudes affect the intention to use AI chatbots in the tourism sector.Method: A quantitative, descriptive-explanatory approach was employed through an online survey distributed to individuals who had prior experience using AI chatbots for travel purposes. A total of 278 valid responses were collected using purposive sampling. The research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS.Result: The findings indicate that perceived ease of use, perceived usefulness, perceived trust, anthropomorphism, and personalization all positively and significantly influence user attitudes toward AI chatbots. Furthermore, attitude was found to exert a strong and significant impact on the intention to use AI chatbots for tourism, confirming its role as a key mediating variable. Among the antecedents, personalization emerged as the most influential factor in shaping user attitudes.Practical Implications for Economic Growth and Development: This study offers valuable insights for AI developers and tourism stakeholders to design more user-centered, trustworthy, and personalized chatbot services. Enhancing the adoption of AI chatbots can improve the efficiency of tourism services, support digital transformation, increase tourist satisfaction, and contribute to sustainable economic growth in the tourism sector.Originality/Value: This study extends the Technology Acceptance Model (TAM) framework by incorporating perceived trust, personalization, and anthropomorphism in the context of AI chatbot adoption from the tourists' perspective in Indonesia.